Distinction between crimes and state offences under our federal constitution - Wan Husain, Wan Ahmad Fauzi (Samudera.my, 2021)
Criminal offences are public law offences thus triable for muslims and non-muslims equally under the federal list. Those criminal offences are also against the precepts of islam, unless proven otherwise.